A study of customer value co-creation in fashion industry: A consumer perspective - Chan, Yan Yee Ashley (2010)
The globalisation of the market for luxury brands has given the luxury fashion industry an ever expanding market and a huge number of consumers yet brand owners are facing challenges in ensuring sufficient customer value in their brands to differentiate themselves. Recent marketing research suggested the traditional good-dominant economy has shifted to service-dominant economy that focuses on personalised brand experiences and value creation processes involving the brand owners and consumers. This study examines the sources of value for luxury fashion brands and identifies the variety of interactions between consumers and manufacturers, the employees and other members in their networks, which help to differentiate the luxury fashion brands and co-create personal experiences and value.